Seaweed-Fish Integrated Aquaculture: A recycle of nutriens from Nile tilapia by Gracilaria changii - Mohd Noor, Ahmad, Prof. Dr; Norahim, Ibrahim; Siti Nordiyana, Md Salim; Noor Hasyierah, Mohd Salleh; Noor Shakimah, Mohamad; Nurul Haniza, Mustapa (Kementerian Pengajian Tinggi Malaysia, 2010)
Prof. Dr. Mohd Noor Ahmad and his team won broze for Seaweed Fish Integrated Aquaculture. IPTA R&D Expo 2005, 30th September - 2nd October 2005 organized by Ministry of Higher Education (MOHE) hosted by Universiti Teknologi Malaysia (UTM).